The role of mesenchymal stem cells in attenuating inflammatory bowel disease through ubiquitination - Liao, Hong Xi; Mao, Xiaojun; Wang, Lan; Wang, Naijian; Ocansey, Dickson Kofi Wiredu; Wang, Bo; Mao, Fei (Frontiers in Immunology, 2024)
Inflammatory bowel disease (IBD), a condition of the digestive tract and one of the autoimmune diseases, is becoming a disease of significant global public health concern and substantial clinical burden. Various signaling pathways have been documented to modulate IBD, but the exact activation and regulatory mechanisms have not been fully clarified, ; thus, the a need for constant exploration of the molecules and pathways that play key roles in the development of IBD. In recent years, several protein post-translational modification pathways, such as ubiquitination, phosphorylation, methylation, acetylation, and glycolysis, have been implicated in IBD. An aberrant ubiquitination in IBD is often associated with dysregulated immune responses and inflammation. Mesenchymal stem cells (MSCs) play a crucial role in regulating ubiquitination modifications through the ubiquitin-proteasome system, a cellular machinery responsible for protein degradation. Specifically, MSCs have been shown to influence the ubiquitination of key signaling molecules involved in inflammatory pathways. This paper reviews the recent research progress in MSC-regulated ubiquitination in IBD, highlighting their therapeutic potential in treating IBD, and offering a promising avenue for developing targeted interventions to modulate the immune system and alleviate inflammatory conditions.